2014
DOI: 10.1136/bjsports-2014-093804
|View full text |Cite
|
Sign up to set email alerts
|

Oral health and elite sport performance

Abstract: While the research base is limited, studies have consistently reported poor oral health in elite athletes since the first report from the 1968 Olympic Games. The finding is consistent both across selected samples attending dental clinics at major competitions and more representative sampling of teams and has led to calls from the International Olympic Committee for more accurate data on oral health. Poor oral health is an important issue directly as it can cause pain, negative effects on appearance and psychos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
2
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(51 citation statements)
references
References 35 publications
1
41
2
7
Order By: Relevance
“…Other studies analyzed the role of the number of training sessions (Zaryski and Smith, 2005), the effect of chronological age (Clemente- Suarez and Nikolaidis, 2017), the contribution of different biomechanical and morphological factors (Hoffman and Fogard, 2011) as well as emotional and personality constructs (Lane and Wilson, 2011), as key performance parameters for ultra-endurance events. Latest studies observed greater performance in ultra-endurance sport events with an appropriated hydration and optimal nutritional status (Peters, 2003;Costa et al, 2014), oral health status and periodontal disease (Needleman et al, 2013(Needleman et al, , 2015Ashley et al, 2015;Frese et al, 2015), higher training intensity and volume (Knechtle et al, 2012), higher pain tolerance (Schutz et al, 2012;Freund et al, 2013) and stress management (Baker et al, 2005;O'Neil and Steyn, 2007). Moreover, a previous study analyzed specific psychological parameters such as the vital commitment, coping with anxiety, self-perception, stress perception and psychological flexibility showing their relationship with athletic performance (Hughes et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Other studies analyzed the role of the number of training sessions (Zaryski and Smith, 2005), the effect of chronological age (Clemente- Suarez and Nikolaidis, 2017), the contribution of different biomechanical and morphological factors (Hoffman and Fogard, 2011) as well as emotional and personality constructs (Lane and Wilson, 2011), as key performance parameters for ultra-endurance events. Latest studies observed greater performance in ultra-endurance sport events with an appropriated hydration and optimal nutritional status (Peters, 2003;Costa et al, 2014), oral health status and periodontal disease (Needleman et al, 2013(Needleman et al, , 2015Ashley et al, 2015;Frese et al, 2015), higher training intensity and volume (Knechtle et al, 2012), higher pain tolerance (Schutz et al, 2012;Freund et al, 2013) and stress management (Baker et al, 2005;O'Neil and Steyn, 2007). Moreover, a previous study analyzed specific psychological parameters such as the vital commitment, coping with anxiety, self-perception, stress perception and psychological flexibility showing their relationship with athletic performance (Hughes et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…While the literature is limited, the relatively poor oral hygiene of elite athletes is often reported. [1617]…”
Section: Discussionmentioning
confidence: 99%
“…[22] This is particularly important among elite athletes where the differences between top competitors are so marginal; these subtle aspects affecting training and performance are key to success. [1722]…”
Section: Discussionmentioning
confidence: 99%
“…32 2012 Londra Olimpiyat Oyunları sırasında diş kliniğine başvuran elit sporcularda yapılan kesitsel çalışmada, 302 sporcuda %55 oranında diş çürüğü ve %76 oranında gingivitis ve %15 oranında periodontitis olduğu bildirilmiştir. [33][34][35][36][37][38] Bu çalışma ile elit sporcuların da ağız sağlığının kötü olabileceği ortaya konmuştur. 33,38 1968 Olimpiyat Oyunları'ndan bugüne kadar elit sporcular üzerinde yapılan çalışmaların sonuçlarından hazırlanan bir konsensüs sonucunda, elit sporcuların ağız-diş sağlığının kötü olduğu, elit sporcularda görülen çürük oranının %15-75, orta ile şiddetli düzeyde periodontal hastalık oranının %15 olduğu bildirilmiştir.…”
Section: Gereç Ve Yöntemlerunclassified
“…33,38 1968 Olimpiyat Oyunları'ndan bugüne kadar elit sporcular üzerinde yapılan çalışmaların sonuçlarından hazırlanan bir konsensüs sonucunda, elit sporcuların ağız-diş sağlığının kötü olduğu, elit sporcularda görülen çürük oranının %15-75, orta ile şiddetli düzeyde periodontal hastalık oranının %15 olduğu bildirilmiştir. 33 Çalışmamız sonucunda ise kadın ve erkek sporcuların çürük diş, eksik diş ve dolgulu diş sayılarının benzer olduğu, diş fırçalama alışkanlıklarının kadın sporcularda erkek sporculara göre daha az sıklıkta olduğu, diş hekimine gitme sıklığının ise kadın sporcularda erkek sporculara göre daha sık olduğu belirlendi. Elde ettiğimiz sonuçlar literatürle örtüşmektedir.…”
Section: Gereç Ve Yöntemlerunclassified